Mathematical Modeling Problem Solving Viewed from Students’ Mathematical Self-Concept on Means-Ends Analysis Based on Blended Learning - Nurochmah, Yeni; Kharisudin, Iqbal (Unnes Journal of Mathematics Education, 2023)
Students are less able to work on mathematical problems due to difficulties understanding information and connecting real problems into mathematical models, resulting in low problem-solving abilities and mathematical self-concept. This study aims to (1) determine students’ problem solving ability with mathematical modeling through the Means-Ends Analysis (MEA) model based on blended learning to achieve classical completeness (2) to determine students’ problem solving ability with mathematical modeling through the MEA model based on blended learning and online PBL learning, (3) to determine the effect of mathematical self-concept on students’ problem solving abilities, (4) describe the students’ problem solving ability with mathematical modeling based on the mathematical self-concept. The research method used was a mixed-method. The population of this study was students of class VIII Junior High School 2 Purbalingga in the academic year 2021/2022, with students of class VIII B (experimental group) and VIII H (control group) taken by simple random sampling method. In the qualitative study, six subjects were taken from the experimental group using purposive sampling. The results showed that the problem-solving ability with mathematical modeling through the MEA model based on blended learning had not yet achieved classical completeness, but the test results with this model were better than the results of the online PBL model. Mathematical self-concept has a positive effect on students' problem solving abilities by 41.3%. Previously, subjects with high mathematical self-concept tended to fulfill all indicators of problem solving ability with mathematical modeling, while subjects with mathematical self-concept tended to have different achievement indicators.